Biochemical Changes Occurring in Yellowfin Tuna Eggs during Embryonic Development - Teruyoshi Tanaka; Tomoki Honryo; Yoshifumi Sawada; Daniel Margulies; Vernon Scholey; Jeanne Wexler; Maria Stein; Amal Biswas; Kenji Takii (Fishes, 2022)
Changes in nutritional constituents and enzyme activities were clarified in yellowfin tuna (YFT, Thunnus albacares) eggs during embryonic development, from eggs immediately after fertilization to hatching. The protein levels in the eggs gradually increased with development until the completion of hatching. In contrast, the triglyceride (TG) and free amino acid (FAA) levels in the eggs gradually declined with embryonic development until hatching was complete, although the energy composition of the FAAs was lower than that of the TGs throughout embryonic development. These results indicate that endogenous TGs are preferentially expended as an energy source during embryonic development. Overall, changes in the activities of aspartate aminotransferase, alanine aminotransferase, creatine kinase, and alkaline phosphatase showed similar patterns throughout development. First, the enzyme levels diminished; then, they remained at constant, low levels just before hatching, when they rapidly increased. This rapid increase was consistent with the protein content, suggesting that organ differentiation and functionalization were promoted during this period. These results will contribute to the establishment of mass-seeding production of YFT.